Pengaruh Zakat Terhadap Sustainable Development Goals di Indonesia (Studi pada Seluruh Provinsi di Pulau Jawa) - Muttaqin, Zainal; Suharsono, Suharsono; Alimuddin, Khasan (QULUBANA: Jurnal Manajemen Dakwah, 2023)
In its development, zakat has become one of the Islamic philanthropic institutions that work for the welfare of society and as an effort to assist in realizing the Sustainable Development Goals (SDGs) program. In fact, the contribution of zakat can not be said to be maximal to the SDGs in Indonesia. This is because the collection and distribution of zakat has not been optimal. This study aims to describe the effect of zakat on the SDGs in Indonesia (a study of all provinces on the island of Java). Of the 17 SDGs programs, only 5 programs were tested, namely (1) economic growth (GRDP), (2) poverty-free (JPM), (3) healthy and prosperous life, quality education, and decent work as measured by the Human Development Index ( HDI), (4) reduced inequality (GI), and (5) gender welfare (GPI). The method used is the Panel Vector Error Correction Model (PVECM). The results of this study prove that (1) Zakat in the short and long term has a negative and significant effect on GRDP, (2) Zakat in the short and long term has no effect on JPM, (3) Zakat in the short and long term has no effect on HDI, (4) Zakat in the short term has no effect on GI, but zakat in the long term has a positive and significant effect on GI, (5) Zakat in the short and long term has no effect on GPI.